PEMBUKTIAN UNSUR SIFAT MELAWAN HUKUM DALAM TINDAK PIDANA PENYUAPAN - Fransiska Novita Eleanora (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2012)
Bribery is part of corruption crime where bribing (bribe) be one of crime type that is most difficult of the verification, which because good of giver bribes (active) and also receiver bribes (passive) be itself crime perpetrator, therefore in the eradication, big possibility that giver bribes and receiver to bribe to be each other protect one another, that the crime becoming not can be asked it the responsibility. Verification of visible bribery crime elements from character is fighting against formal law and material.